Stationary Boulders Increase River Seismic Frequency via Turbulence - Nativ, Ron; Turowski, Jens M.; Chang, Jui‐Ming; Hovius, Niels; Yang, Ci‐Jian; Chen, Wen‐Sheng; Chang, Wen‐Yen; Laronne, Jonathan B. (Geophysical research letters, 2025)
Despite a century of research, turbulent flows mobilizing bedload remain elusive, while seismic waves generated by surface processes can unravel river dynamics. We studied the seismic signals emitted near rivers in two tributaries characterized by large boulders. Data show an unusually high dominant seismic frequency, reaching >2 times the frequency observed in nearby smoother channels. Consistent high‐frequency content during periods without bedload transport prompts the hypothesis that turbulence is a key contributor to generating higher frequencies. Assuming that dominant turbulent eddies decrease in size due to boulder‐constrained flow, we formulate a frequency scaling relationship that aligns well with field data. A positive relationship of the frequency with water depth breaks at bedload onset, indicating that dissipation of flow energy partitions between turbulence and bedload transport. Our study shows that seismic frequency captures contrasting bed morphologies in mountain streams, offering insights into flow‐roughness interactions. Plain Language Summary River processes, like water flow and sediment transport, generate energy that turns into seismic waves traveling through the ground. Studying these waves allows researchers to gain insights into how rivers function. We compared energy from rivers with large boulders to nearby streams with smoother surfaces. We found that boulder‐rich rivers produce higher seismic frequencies as the boulders reduce the size of turbulence‐related eddies. Our study shows how analyzing seismic energy helps to understand river dynamics, including flow and sediment transport. Key Points Boulder‐bed channels in the Liwu River, Taiwan, exhibit higher seismic frequency than channels with smoother beds The higher seismic frequencies are due to a reduction of turbulent eddy sizes constrained by boulder spacing The frequency‐depth relationship in seismic data shifts during and after bedload transport, likely due to energy partitioning or changes in bed roughness